An investigation of fitness analysis and risk analysis: a systematic review / Amira Farzana Abdul Kahar, Ellail Ain Mohd Aznan and Ahmad Fikri Mohd Kassim - Abdul Kahar, Amira Farzana; Mohd Aznan, Ellail Ain; Mohd Kassim, Ahmad Fikri (Universiti Teknologi MARA, Perlis, 2021)
Risk analysis consists of three elements which are risk management, risk communication, and risk assessment. The risk occurs in many ways and conditions while exercising mostly in the fitness industry. Therefore, the purpose of this study aims to examine the currently available literature that focuses on risk analysis and fitness facilities in the fitness industry. A comprehensive survey of online data sources (Scopus and Web of Science All Collection), as well as conference proceedings of possibly related papers, were analyzed. The search was limited to research that was published in English and had complete text access. All of these resources were gone through, using key search words and equivalents for fitness facilities, fitness centres with risk analysis, risk management, risk communication and risk assessment. 33 studies were record screened from 94 total number of records after duplicate and only a few studies were accepted for review which is eight theses was selected in qualitative synthesis and seven studies selected in the quantitative synthesis. The data were sort from the two published studies (Scopus and Web of Science). Results found that 15 dissertations and/or theses were submitted to systematic quality analysis. The findings systematically evaluate cross-sectional observation-based studies indicating risk analysis is critical for maintaining the fitness industry's surroundings safe and pristine when participating in any physical activity, particularly at a fitness facility. Analyses suggest that the assumption that risk analysis has a significant influence on the impression of being able to control future accidents. In conclusion, applying the management of risk analysis in fitness facilities is important in the fitness industry.